2011
DOI: 10.1007/s00586-011-1907-2
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented lumbar arthrodesis in elderly patients: prospective study using cannulated cemented pedicle screw instrumentation

Abstract: Introduction Lumbar fusion in elderly patients is increasingly common. This study prospectively investigated the clinical and radiological outcome of osteoporotic patients [70 years with degenerative lumbar instability treated with fusion using a new cannulated, cemented, pedicle screw instrumentation augmented with PMMA. Materials and Methods The surgical protocols, patient records, densitometry, imaging studies, and pre-and postoperative patient-reported outcome questionnaires of 23 patients (mean age, 77 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 26 publications
0
43
0
1
Order By: Relevance
“…This biomechanical mismatch creates shielding effects on adjacent vertebral bodies, eventually causing compressive fracture or adjacent disk disease. 16 Also, in cases where pedicle screws need to be retrieved or removed from the screw-cement-bone complex, this becomes extremely difficult or even impossible, due to the excessive bonding strength between screws and the cement. 17 Most importantly, due to its nondegradability and inertness, PMMA cannot form a biological bonding with bone, nor can it induce bone ingrowth or integration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This biomechanical mismatch creates shielding effects on adjacent vertebral bodies, eventually causing compressive fracture or adjacent disk disease. 16 Also, in cases where pedicle screws need to be retrieved or removed from the screw-cement-bone complex, this becomes extremely difficult or even impossible, due to the excessive bonding strength between screws and the cement. 17 Most importantly, due to its nondegradability and inertness, PMMA cannot form a biological bonding with bone, nor can it induce bone ingrowth or integration.…”
mentioning
confidence: 99%
“…In addition, when considering the cases of postoperation infection, the nondegradable PMMA becomes another risk factor for both deep infection and superficial infection. 16 These drawbacks associated with PMMA yield an unmet need of robust but bioactive or bioabsorbable bone cement for better biomechanical outcomes of cannulated pediclescrew fixation. In the present study, a novel injectable calcium phosphate-based nanocomposite (CPN) was designed and prepared to meet the needs of cannulated pedicle-screw fixation for improved efficacy and biomechanical stability.…”
mentioning
confidence: 99%
“…4,5 Many studies have shown that when bone cement is used to augment pedicle screws, it can significantly increase the rigidity, stiffness, and strength of the screw. 3,8 Various systems and techniques for using cement to augment osteoporotic bone have been developed, such as expandable screws, partially or fully cannulated screws, 9,12 and direct 2 or indirect injections. In recent years, percutaneous pedicle screw fixation, which limits muscular damage and intraoperative bleeding, decreases postoperative pain and accelerates postoperative recovery.…”
mentioning
confidence: 99%
“…So far, the augmentation of pedicle screws with PMMA has demonstrated to be the most efficient solution to enhance screw strength in osteoporotic bone [2][3][4][5][6][7]. It has shown clinical efficacy in the management of degenerative disease [17] and fractures [18][19][20]. However, there is a concern about the ideal time for augmentation during the surgical procedure, especially if a restoration or a derotation maneuver of the instrumented vertebra is part of the surgery.…”
Section: Discussionmentioning
confidence: 99%